Using Willingness to Pay to Evaluate the Implementation of Canada’s Residential Radon Exposure Guideline - Spiegel, Jerry M. (Can J Public Health, 2002)
Background: The objective of this investigation was to determine the effectiveness of Canada’s residential radon exposure guideline in influencing individuals’ health protection decisions. Method: Homeowners with known exposure levels in a high residential radon area (Winnipeg, Manitoba) were surveyed to document what they had done and spent to reduce their exposure to radon. The 507 respondents were then re-surveyed to elucidate their response to hypothetical scenarios. Logistic regression was used to model risk reduction decisions as a function of exposure and other explanatory variables. Results: Homeowners were only likely to have taken action to reduce exposure at levels exceeding 1,100 Bq/m(3), well above Canada’s guideline of 800 Bq/m(3). However, when informed of the guideline, respondents indicated they would act at exposures of 702 Bq/m(3). Interpretation: The Canadian residential radon exposure guideline, as it has been implemented, has not effectively prompted homeowner actions to reduce exposures to radon.